2021
DOI: 10.1002/acn3.51473
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography in multiple sclerosis: A 3‐year prospective multicenter study

Abstract: Objective: To evaluate changes over 3 years in the thickness of inner retinal layers including the peripapillary retinal nerve fiber layer (pRNFL), and combined macular ganglion cell and inner plexiform layers (mGCIPL), in individuals with relapsing-remitting multiple sclerosis (RRMS) versus healthy controls; to determine whether optical coherence tomography (OCT) is sufficiently sensitive and reproducible to detect small degrees of neuroaxonal loss over time that correlate with changes in brain volume and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 46 publications
4
31
5
2
Order By: Relevance
“…18,32 Regarding the latter, aLGCIPL of 0.20 µm and aLpRNFL of 0.52 µm are expected in healthy controls, 26,33,34 which is substantially lower than the mean aLGCIPL and aLpRNFL of 1.0-1.6 and 1.0-1.3 µm observed in this study, respectively. In turn, in comparison to longitudinal data provided by the abovementioned OCTiMS study, 17 aLGCIPL and aLpRNFL in our cohort were slightly higher, which may partly be explained by distinct inclusion criteria and methodological differences.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…18,32 Regarding the latter, aLGCIPL of 0.20 µm and aLpRNFL of 0.52 µm are expected in healthy controls, 26,33,34 which is substantially lower than the mean aLGCIPL and aLpRNFL of 1.0-1.6 and 1.0-1.3 µm observed in this study, respectively. In turn, in comparison to longitudinal data provided by the abovementioned OCTiMS study, 17 aLGCIPL and aLpRNFL in our cohort were slightly higher, which may partly be explained by distinct inclusion criteria and methodological differences.…”
Section: Discussioncontrasting
confidence: 66%
“…While within the OCTiMS trial, no robust association between retinal layer thinning and performance in SDMT could be demonstrated, and a recently published study observed an association between attention and executive function tests and retinal layer thickness. 17,31 Despite some advantages of GCIPL over pRNFL and more pronounced effects in EDSS than in SDMT prognostication, the findings of the present study demonstrate that the prognostic value to predict disability progression still prevails after a long-term follow-up of approximately 6 years. This prognostic potential is based on (1) smaller values of baseline thickness of retinal layers and (2) higher annual thinning rates of retinal layers.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This preexisting subclinical disease leads to the fact that firstly in MRI chronic inflammation with demyelination and axonal damage may already be detectable at the time of first clinical onset ( Bjornevik, Munger, and Cortese, 2020 , Borgström et al, 2020 ). Further, cohort analyses using OCT in patients with early MS have consistently shown that retinal neuroaxonal damage is predominantly present at the initial clinical phase of MS and independent of clinical optic nerve involvement compared with matched healthy controls ( Borgström et al, 2020 , Petzold, Balcer, and Calabresi, 2017 , Martinez-Lapiscina, Arnow, and Wilson, 2016 , Paul, Calabresi, and Barkhof, 2021 ). Lastly, it is also known that the presence of CSF-specific OCBS i) has a high positive predictive value for MS and ii) is associated with a significantly increased risk of conversion to MS in patients with a clinically isolated syndrome ( Calabrese et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…[5][6][7] Optical coherence tomography (OCT) allows the rapid quantification of the thickness of retinal neuroaxonal layers, and studies using OCT have demonstrated that rates of macular ganglion cell + inner plexiform layer (GCIPL) and peripapillary retinal nerve fiber layer (pRNFL) thinning are accelerated in people with MS, independently of overt episodes of inflammatory activity involving the anterior visual pathway (i.e., acute optic neuritis [ON]), and are associated with longitudinal brain atrophy. [8][9][10][11] Furthermore, rates of retinal layer thinning are faster in progressive MS, as compared with relapsing-remitting MS (RRMS), with accelerated deeper retinal layer thinning (inner nuclear layer [INL] and outer nuclear layer [ONL]) appearing to be more specific features of progressive MS. 10,12,13 Given the above, OCT-derived retinal measures have been proposed as a biomarker of progressive, diffuse neurodegeneration in MS and assessing associations with sNfL is clearly of significant interest. However, only a few studies have examined this issue and have produced conflicting findings.…”
mentioning
confidence: 99%